2017
DOI: 10.1002/lary.26729
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of 18fluorodesoxyglucose positron emission/computed tomography and magnetic resonance imaging in detecting T1‐T2 head and neck squamous cell carcinoma

Abstract: 4. Laryngoscope, 128:378-385, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 49 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…Despite this, recent studies have observed certain scenarios wherein [ 18 F]FDG PET/CT can be more powerful in terms of accuracy than neck MRI. A study of 35 patients by Chaput et al showed that [ 18 F]FDG PET/CT had greater diagnostic accuracy, with a sensitivity of 83%, compared to MRI, which was only 63% sensitive for detecting head-and-neck cancers in patients in the T1-T2 category [15]. This suggests that [ 18 F]FDG PET/CT is more effective in lower-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, recent studies have observed certain scenarios wherein [ 18 F]FDG PET/CT can be more powerful in terms of accuracy than neck MRI. A study of 35 patients by Chaput et al showed that [ 18 F]FDG PET/CT had greater diagnostic accuracy, with a sensitivity of 83%, compared to MRI, which was only 63% sensitive for detecting head-and-neck cancers in patients in the T1-T2 category [15]. This suggests that [ 18 F]FDG PET/CT is more effective in lower-stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…Because the CNNs were trained on multiparametric data, some errors—especially on the GTV edges—are present in the ground-truth labels, leading to worse segmentation results than in rigid body areas. In addition, the interobserver variability of head and neck cancer is already much higher than, for example, that of the brain tumors (49, 50). Despite the intrinsic limitation on image quality, the trained network yielded good tumor segmentations, and it was shown that distortion correction of ADC data does not significantly improve segmentation performance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 35 patients by Chaput et al showed greater diagnostic accuracy with higher sensitivity of FDG PET/CT (83%) compared to MRI (63%) for detection of T1-T2 category head and neck SCCa, suggesting efficacy of FDG PET/CT in lower stage disease. 10 When PET is performed with a contrast enhanced CT, diagnostic CT images can be obtained from a single examination and may obviate the need for additional imaging for staging (CT or MR). 11 Of note, at our institution, all PET/CT exams are performed with iodinated IV contrast unless there are medical contraindications for the patient (contrast allergy or renal insufficiency).…”
Section: Primary Tumormentioning
confidence: 99%